Anti-NMDA receptor encephalitis presenting as isolated aphasia in an adult. Issue 4 (4th July 2018) - Constantinides, Vasilios C.; Kasselimis, Dimitrios S.; Paraskevas, George P.; Zacharopoulou, Maria; Andreadou, Elisabeth; Evangelopoulos, Maria-Eleftheria; Kapaki, Elisabeth; Kilidireas, Costas; Stamboulis, Eleftherios; Potagas, Constantin
ABSTRACT: Anti-NMDA receptor (NMDA-r) encephalitis is a relatively rare cause of autoimmune encephalitis with divergent clinical presentations. We report a case of an adult patient with anti-NMDA-r encephalitis presenting with isolated, abrupt-onset aphasia. Her condition remained unaltered over a period of 6 months. The patients' electroencephalogram findings were typical for NMDA-r encephalitis; however, her magnetic resonance imaging and cerebrospinal fluid analysis were normal. She responded well to immunotherapy, and aphasia eventually resolved. The natural course of the present case contradicts the rapidly progressive nature of typical NMDA-r encephalitis. Furthermore, it broadens the clinical spectrum of anti-NMDA-r encephalitis, to incorporate isolated, nonprogressive aphasia.